On the successful chemical recycling of carbon fiber/epoxy resin composites under the mild condition. (20th October 2017) - Jiang, Jianjun; Deng, Guoli; Chen, Xing; Gao, Xinyu; Guo, Qiang; Xu, Chumeng; Zhou, Linchao
Abstract: The research of green chemical recycling of thermosetting carbon fiber composites has been widely concerned by scholars. In this paper, the recycling of high-performance carbon fiber epoxy/resin composites(CF/EP) were conducted in a shorter time and at much lower temperature than those reported recycling methods. The CF/EP were pretreated in nitric acid to be initially decomposed and layered, then the layered CF/EP were subjected to macrogol 400 in presence of potassium hydroxide at 160 °C for 200min. As a result, the carbon fiber was separated and recovered from epoxy resin. Specifically, resin removal rate was more than 95 wt%, and the tests of X-ray photoelectron spectra and scanning electron microscope revealed that surface of recovered fiber was close to that of virgin fiber. In addition, dynamic contact angle meter shown that surface wettability of recovered fiber was improved, which might contribute to the infiltration of resin. On the other hand, the mechanical properties of recovered carbon fiber decreased slightly compared with those of virgin fiber. As mentioned above, the recycling of CF/EP was realized under mild conditions and the performance of recovered carbon fiber was well preserved. This means that the efficient method to recover CF/EP showed great commercial application potential.